The status of indochinese grey langur Trachypithcus crepusculus at Xuan Lien nature reserve, Thanh Hoa province - Hai, Nguyen Dinh; Nghia, Nguyen Xuan; Dang, Nguyen Xuan; Phuong, Dang Huy; Toan, Nguyen Mau (Academia Journal of Biology, 2016)
Field surveys and interviewing local residents and forest rangers from 2013 to 2015 in Xuan Lien Nature Reserve have recorded 7 groups/troops of Indochinese grey langur (5 groups were sighted and 2 groups recorded by from interview). Each group consistS of 30-35 individuals as maximum and total of 100-200 individuals of Indochinese grey langurs was estimated to exist in the reserve. For all recorded groups, each group consists of at least on adult male, several adult females and sub-adults, and four groups have juveniles. The langurs were found in 4 little-affected forest types (Limestone evergreen forest, Sub-tropical evergreen forest, Lowland evergreen forest and Mixed wood-bamboo forest) located in 8 forest compartments which are situated far away from human settlements. The population of Indochinese grey langur in Xuan Lien NR is among the largest populations of this species in Vietnam. The population is facing with many threats such as wildlife hunting/trapping; Forest habitat degradation; Illegal timber poaching; Habitat disturbance by illegal encroachment of local residents and free-ranging cattle raising. Recommended measures for conservation of the langur population in Xuan Lien NR includestrengthening enforcement of forest and wildlife protection laws; promotion of natural regeneration of forest habitat; awareness education for local residents; monitoring of the langur population and habitat state; study of the species ecological requirement and investigation of Indochinese grey langur population in adjacent Pu Hoat Nature Reserve for collaborative actions on the species conservation.